Reclaimed oil bio-based plastic mixed rubber sole material and preparation method thereof
By combining recycled oil bio-based plastics with other modified materials and forming a crosslinking network structure through vulcanization treatment, the shortcomings of traditional rubber sole materials in terms of mechanical properties and environmental sustainability are solved, and the high performance and long life of the sole are achieved.
Patent Information
- Application Number
- CN202510274516.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional rubber sole materials have shortcomings in mechanical properties and environmental sustainability, and lack antibacterial ability, resulting in short service life and uncomfortable wearing.
The combination of recycled oil bio-based plastics, smoke glue, modified mixed reinforcement filler, calcium powder, diisopropyl oxide, zinc oxide, stearic acid, octylated dianiline and antibacterial and anti-mold filler is used to form a cross-linking network structure through vulcanization treatment to improve the mechanical properties and antibacterial properties of the material.
It improves the bending performance, wear comfort and durability of the sole, while enhancing the antibacterial and mildew resistance, and extends the service life of the sole.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber soles, in particular to a recycled oil bio-based plastic mixed rubber sole material and a preparation method thereof. Background Art
[0002] Traditional sole materials are mainly rubber, which has the advantages of good elasticity, wear resistance and anti-slip properties, and can meet the basic needs of soles in daily wear and various sports scenarios. However, with the increasing shortage of global resources and the increasing awareness of environmental protection, traditional rubber sole materials face many challenges. In recent years, bio-based plastics have gradually emerged as an emerging material. Bio-based plastics are derived from renewable biomass resources, such as plant starch, cellulose, etc. Their production process has the advantage of lower carbon emissions than petroleum-based plastics, which helps to reduce dependence on petroleum resources and is in line with the concept of green environmental protection and sustainable development. However, when bio-based plastics are used alone as sole materials, their mechanical properties are insufficient in some aspects. For example, their strength, toughness and elastic recovery may not be as good as traditional rubber, and it is difficult to fully meet the performance requirements of soles under complex stress conditions.
[0003] As a product of resource recycling, recycled oil has certain economic value and reusability. It can come from various channels such as waste lubricating oil, animal and plant oils and fats. Introducing recycled oil into the sole material system can not only realize the resource utilization of waste, but also improve the processing performance and certain physical properties of the material.
[0004] The existing rubber sole materials do not have antibacterial and antimicrobial capabilities, and the service life of the soles is short; and the rubber sole materials cannot adapt well to bending and deformation during wearing, and have low wearing comfort and poor durability. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a recycled oil bio-based plastic mixed rubber sole material and a preparation method thereof, which solves the above-mentioned problems.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a recycled oil bio-based plastic mixed rubber sole material, composed of the following materials by weight: 40-60 parts of recycled oil bio-based plastic, 20-30 parts of smoked rubber, 10-15 parts of modified mixed reinforcing filler, 10-20 parts of calcium powder, 0.5-1.0 parts of diisopropylbenzene oxide, 1.0-1.5 parts of zinc oxide, 0.5-0.8 parts of stearic acid, 1.5-2.5 parts of octylated diphenylamine and 4-6 parts of antibacterial and mildew-proof filler; The modified mixed reinforcing filler is prepared by the following steps: A1. Fiber alkali washing and activation: Soak the bamboo fiber and carbon fiber in potassium hydroxide solution for 1-1.5 hours at a temperature of 40-45°C to remove impurities on the fiber surface and generate active sites. After soaking, rinse with plenty of water until neutral, and then dry at 80-85°C for 2-2.5 hours; A2, silane coupling agent grafting, add the dried bamboo fiber and carbon fiber to the silane coupling agent solution respectively, the mass ratio of bamboo fiber to silane coupling agent is 12:1-10:1, the mass ratio of carbon fiber to silane coupling agent is 15:1-13:1, stir and react at 50-55°C for 2-2.5 hours, this step makes the fiber surface grafted with silane coupling agent, enhances the reactivity and compatibility of the fiber with subsequent monomers, after the reaction, filter and wash the fibers respectively, and dry at 70-75°C for 1-1.5 hours; A3, copolymerization grafting and cross-linking reaction, the bamboo fiber grafted with silane coupling agent and the carbon fiber are mixed, added to a toluene solution containing butyl acrylate, glycidyl methacrylate mixed monomer, initiator azobisisobutyronitrile and cross-linking agent polyethylene glycol diacrylate, and stirred at 75-80°C for 3-3.5 hours under nitrogen protection; during the reaction, the mixed monomer undergoes polymerization under the action of the initiator and is grafted onto the fiber surface, and the cross-linking agent forms a cross-linked structure between the grafted polymer chains, thereby improving the fiber's strength, toughness and heat resistance. The long-chain alkyl structure of butyl acrylate helps to increase flexibility; the initiator decomposes to produce free radicals, which then initiates monomer polymerization, and the polymer chain continues to grow and is grafted onto the fiber surface, while polyethylene glycol diacrylate participates in the cross-linking reaction; after the reaction, filter and wash the fiber, and dry it at 60-65°C for 1-1.5 hours; A4, surface modification and dispersion treatment, put the copolymerized grafted mixed fiber into an ethanol solution containing stearyl glyceride, and stir the reaction at 40-45°C for 1.5-2 hours. Stearyl glyceride physically adsorbs or chemically bonds with the active groups or grafted polymers on the fiber surface, plays a role in lubrication and improving dispersibility, and its ester structure also helps to improve flexibility to a certain extent. After the reaction is completed, filter and wash the fiber, and dry it at 50-55°C for 1-1.5 hours to obtain a modified mixed reinforcing filler.
[0007] Preferably, the concentration of the silane coupling agent solution in A2 is 2-3%, wherein the solvent is ethanol.
[0008] Preferably, the amount of the glycidyl methacrylate mixed monomer in A3 is 25-35% of the total mass of the fiber, the amount of the initiator azobisisobutyronitrile is 0.8-1.2% of the mass of the mixed monomer, and the amount of the crosslinking agent polyethylene glycol diacrylate is 0.4-0.8% of the mass of the mixed monomer.
[0009] Preferably, the amount of glyceryl stearate in A4 is 4-8% of the total mass of the fiber; and the concentration of the ethanol solution is 4-8%.
[0010] Preferably, the antibacterial and mildew-proof filler is composed of the following raw materials in parts by weight: 2-3 parts of nano copper oxide, 2-3 parts of trimethyloctadecylsilane quaternary ammonium salt, 3-4 parts of sepiolite powder and 0.5-1 part of vinyl triethoxysilane.
[0011] The antibacterial and mildew-proof filler is prepared by the following steps: B1. Surface modification of nano copper oxide: disperse nano copper oxide in an ethanol solution, perform ultrasonic treatment for 40-60 minutes to make it uniformly dispersed, then slowly drop vinyl triethoxy silane, and stir and react at 40-45°C for 2-3 hours; after the reaction, centrifuge, wash with ethanol 3-5 times, and dry at 60-70°C for 2-3 hours; this step enables the surface of nano copper oxide to be grafted with vinyl triethoxy silane, improves its compatibility and binding force with organic antibacterial agents and sepiolite powder, and enhances the stability of the antibacterial filler; B2, compounding the antibacterial agent with sepiolite powder, dissolving the organosilicon quaternary ammonium salt antibacterial agent in toluene solution, adding it to the sepiolite powder, stirring and reacting at 50-55°C for 3-4 hours, and the amount of the antibacterial agent is 50-60% of the mass of the sepiolite powder. After the reaction, vacuum drying is performed at 80-90°C for 4-5 hours to fully load the antibacterial agent in the pore structure of the sepiolite powder to form a composite carrier with antibacterial function; B3, composite and secondary modification of nano copper oxide with composite carrier, add the surface modified nano copper oxide to the above-mentioned antibacterial agent and sepiolite powder composite, add ethanol, stir evenly, then add γ-aminopropyltriethoxysilane dropwise, and stir and react at 45-50°C for 2.5-3.5 hours. After the reaction is completed, filter, wash with ethanol 2-4 times, and dry at 70-80°C for 3-4 hours. This step further enhances the bonding force between nano copper oxide and the composite carrier, and the introduction of vinyltriethoxysilane helps to improve the dispersibility of the filler in the sole material and has a certain improvement effect on the material's anti-cracking performance; B4, cross-linking modification, the product obtained in the third step is mixed with an isocyanate cross-linking agent in a toluene solution, and stirred at 60-70°C for 1.5-2.5 hours. During the reaction, the cross-linking agent reacts with the active groups on the surface of the filler to form a cross-linked network structure, which significantly improves the integrity and stability of the filler, effectively prevents the occurrence of cracking, and does not affect its antibacterial properties. After the reaction is completed, the final modified antibacterial and mildew-proof filler is obtained through filtration, washing, and drying.
[0012] Preferably, the concentration of the ethanol solution in B1 is 6-8%; the mass ratio of vinyltriethoxysilane to nano-copper oxide is 1:4-1:3.
[0013] Preferably, the concentration of the toluene solution in B2 is 10-15%.
[0014] Preferably, the concentration of the ethanol solution in B3 is 6-8%; the amount of γ-aminopropyltriethoxysilane used is 0.3-0.5% of the total mass.
[0015] Preferably, the isocyanate crosslinking agent in B4 is toluene diisocyanate, and the amount used is 1-2% of the total mass; the drying temperature is 80-90° C., and the drying time is 3-5 hours.
[0016] A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 30-50 rpm, the speed of the roller of the open mixer to 10-15 rpm, and the mixing temperature to 80-100°C; perform preliminary mixing for 5-10 minutes to evenly mix the two to form a continuous matrix phase; S3. Then add 10-15 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 10-15 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 50-70 rpm, and the temperature can be controlled at 100-120℃; the speed of the open mill roller can be increased to 15-20 rpm.
[0017] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 10-15 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 60-80 rpm, the temperature is 120-140°C; the speed of the open mill roller is 20-25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 150-180°C, the vulcanization pressure to 10-15MPa, and the vulcanization time to 10-30 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0018] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed.
[0019] The present invention provides a recycled oil bio-based plastic mixed rubber sole material and a preparation method thereof. It has the following beneficial effects: By combining the flexibility and elasticity of recycled oil bio-based plastics with the natural rubber elasticity and resilience of smoked rubber, the sole has good bending properties, can adapt to various deformation movements of the foot during walking and exercise, and provide a comfortable wearing experience. At the same time, it is not easy to crack or break after repeated bending, ensuring the durability of the sole.
[0020] By adding modified hybrid reinforcing fillers, butyl acrylate monomers containing long-chain alkyl groups are used to replace part of the original rigid monomers, and stearic acid glyceryl is used for surface treatment. Through the adjustment and replacement of these functional groups, it is expected that the flexibility of the entire modified hybrid reinforcing filler can be increased, so that when it is used in recycled oil bio-based plastic modified rubber sole materials, it can better adapt to the bending and deformation of the sole during wearing, thereby improving the wearing comfort and durability of the sole.
[0021] The modified antibacterial and mildew-proof filler prepared by modification reaction gives full play to the antibacterial advantages of nano-copper oxide and organosilicon quaternary ammonium salt antibacterial agent. At the same time, with the help of the characteristics of sepiolite powder and multiple modification treatments, the dispersion of the filler in the sole material, the bonding strength with the material and the anti-cracking performance are effectively improved, giving priority to meeting the requirements of antibacterial effect and taking into account the anti-cracking performance, so that it can be better used in recycled oil bio-based plastic mixed rubber sole materials to improve the comprehensive performance and service life of the sole. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1,
[0023] The present invention provides a technical solution: the modified mixed reinforcing filler is prepared by the following steps: A1. Fiber alkali washing and activation: Soak the bamboo fiber and carbon fiber in potassium hydroxide solution for 1 hour at 40°C to remove impurities on the fiber surface and generate active sites. After soaking, rinse with plenty of water until neutral, and then dry at 80°C for 2 hours. A2, silane coupling agent grafting, the dried bamboo fiber and carbon fiber are added to the silane coupling agent solution, the mass ratio of bamboo fiber to silane coupling agent is 12:1, the mass ratio of carbon fiber to silane coupling agent is 15:1, and the reaction is stirred at 50°C for 2 hours. This step makes the fiber surface grafted with silane coupling agent to enhance the reactivity and compatibility of the fiber with subsequent monomers. After the reaction, the fiber is filtered and washed, and dried at 70-75°C for 1 hour; the concentration of the silane coupling agent solution is 2%, and the solvent is ethanol.
[0024] A3, copolymerization grafting and cross-linking reaction, the bamboo fiber grafted with silane coupling agent and the carbon fiber are mixed, added into a toluene solution containing butyl acrylate, glycidyl methacrylate mixed monomer, initiator azobisisobutyronitrile and cross-linking agent polyethylene glycol diacrylate, and stirred at 75°C for 3 hours under nitrogen protection; during the reaction, the mixed monomer undergoes polymerization reaction under the action of the initiator and is grafted onto the fiber surface, and the cross-linking agent forms a cross-linking structure between the grafted polymer chains, thereby improving the strength, toughness and heat resistance of the fiber. The long-chain alkyl structure of butyl acrylate helps to increase flexibility; the initiator decomposes to produce free radicals, which then initiate monomer polymerization. The polymer chain continues to grow and is grafted to the fiber surface. At the same time, polyethylene glycol diacrylate participates in the cross-linking reaction; after the reaction, the fiber is filtered, washed, and dried at 60°C for 1 hour; the amount of glycidyl methacrylate mixed monomer is 25% of the total mass of the fiber, the amount of initiator azobisisobutyronitrile is 0.8% of the mass of the mixed monomer, and the amount of cross-linking agent polyethylene glycol diacrylate is 0.4% of the mass of the mixed monomer.
[0025] A4, surface modification and dispersion treatment, put the copolymerized grafted mixed fiber into an ethanol solution containing stearyl glycerol, and stir the reaction at 40°C for 1.5 hours. Stearyl glycerol physically adsorbs or chemically bonds with the active groups or grafted polymers on the fiber surface, plays a role in lubrication and improving dispersibility, and its ester structure also helps to improve flexibility to a certain extent. After the reaction, filter and wash the fiber, dry it at 50°C for 1 hour, and obtain a modified mixed reinforcing filler. The amount of stearyl glycerol is 4% of the total mass of the fiber; the concentration of the ethanol solution is 4%. Embodiment 2,
[0026] The present invention provides a technical solution: the modified mixed reinforcing filler is prepared by the following steps: A1. Fiber alkali washing and activation: Soak the bamboo fiber and carbon fiber in potassium hydroxide solution for 1.5 hours at 45°C to remove impurities on the fiber surface and generate active sites. After soaking, rinse with plenty of water until neutral, and then dry at 85°C for 2.5 hours. A2, silane coupling agent grafting, the dried bamboo fiber and carbon fiber are added to the silane coupling agent solution, the mass ratio of bamboo fiber to silane coupling agent is 10:1, the mass ratio of carbon fiber to silane coupling agent is 13:1, and the reaction is stirred at 55°C for 2.5 hours. This step makes the fiber surface grafted with silane coupling agent to enhance the reactivity and compatibility of the fiber with subsequent monomers. After the reaction, the fiber is filtered and washed, and dried at 75°C for 1.5 hours; the concentration of the silane coupling agent solution is 3%, and the solvent is ethanol.
[0027] A3, copolymerization grafting and cross-linking reaction, the bamboo fiber grafted with silane coupling agent and the carbon fiber are mixed, added into a toluene solution containing butyl acrylate, glycidyl methacrylate mixed monomer, initiator azobisisobutyronitrile and cross-linking agent polyethylene glycol diacrylate, and stirred at 80°C for 3.5 hours under nitrogen protection; during the reaction, the mixed monomer undergoes polymerization reaction under the action of the initiator and is grafted onto the fiber surface, and the cross-linking agent forms a cross-linking structure between the grafted polymer chains, thereby improving the strength, toughness and heat resistance of the fiber. The long-chain alkyl structure of butyl acrylate helps to increase flexibility; the initiator decomposes to produce free radicals, which then initiate monomer polymerization. The polymer chain continues to grow and is grafted to the fiber surface. At the same time, polyethylene glycol diacrylate participates in the cross-linking reaction; after the reaction, the fiber is filtered, washed, and dried at 65°C for 1.5 hours; the amount of glycidyl methacrylate mixed monomer is 35% of the total mass of the fiber, the amount of initiator azobisisobutyronitrile is 1.2% of the mass of the mixed monomer, and the amount of cross-linking agent polyethylene glycol diacrylate is 0.8% of the mass of the mixed monomer.
[0028] A4, surface modification and dispersion treatment, put the copolymerized grafted mixed fiber into an ethanol solution containing stearyl glycerol, and stir and react at 45°C for 2 hours. Stearyl glycerol physically adsorbs or chemically bonds with the active groups or grafted polymers on the fiber surface, plays a role in lubrication and improving dispersibility, and its ester structure also helps to improve flexibility to a certain extent. After the reaction, filter and wash the fiber, dry it at 55°C for 1.5 hours, and obtain a modified mixed reinforcing filler. The amount of stearyl glycerol is 8% of the total mass of the fiber; the concentration of the ethanol solution is 8%. Embodiment 3,
[0029] The invention provides a technical solution: the antibacterial and mildew-proof filler is composed of the following raw materials in parts by weight: 2 parts of nano copper oxide, 2 parts of trimethyl octadecylsilane quaternary ammonium salt, 3 parts of sepiolite powder and 0.5 parts of vinyl triethoxysilane.
[0030] The antibacterial and mildew-proof filler is prepared by the following steps: B1. Surface modification of nano copper oxide: disperse nano copper oxide in an ethanol solution, perform ultrasonic treatment for 40 minutes to make it uniformly dispersed, then slowly drop vinyl triethoxy silane, and stir and react at 40°C for 2 hours; after the reaction, centrifuge, wash with ethanol 3 times, and dry at 60°C for 2 hours; the concentration of the ethanol solution is 6%; the mass ratio of vinyl triethoxy silane to nano copper oxide is 1:4; this step enables the surface of nano copper oxide to be grafted with vinyl triethoxy silane, improves its compatibility and binding force with organic antibacterial agents and sepiolite powder, and enhances the stability of the antibacterial filler; B2, compounding the antibacterial agent with sepiolite powder, dissolving the organosilicon quaternary ammonium salt antibacterial agent in a toluene solution with a concentration of 10%, adding it to the sepiolite powder, stirring and reacting at 50°C for 3 hours, and the amount of the antibacterial agent is 50% of the mass of the sepiolite powder. After the reaction, vacuum drying is performed at 80°C for 4 hours to fully load the antibacterial agent into the pore structure of the sepiolite powder to form a composite carrier with antibacterial function; B3. Composite and secondary modification of nano-copper oxide and composite carrier. Add the surface-modified nano-copper oxide to the above-mentioned antibacterial agent and sepiolite powder composite, add ethanol, stir evenly, then add γ-aminopropyltriethoxysilane dropwise, and stir and react at 45°C for 2.5 hours. After the reaction is completed, filter, wash with ethanol twice, and dry at 70°C for 3 hours. The concentration of ethanol solution is 6%; the amount of γ-aminopropyltriethoxysilane is 0.3% of the total mass. This step further enhances the bonding force between nano-copper oxide and the composite carrier. At the same time, the introduction of vinyltriethoxysilane helps to improve the dispersibility of the filler in the sole material and has a certain improvement effect on the material's anti-cracking performance; B4, cross-linking modification, the product obtained in the third step is mixed with an isocyanate cross-linking agent in a toluene solution, and stirred at 60°C for 1.5 hours. The isocyanate cross-linking agent is toluene diisocyanate, and the amount is 1% of the total mass; the drying temperature is 80°C, and the drying time is 3 hours. During the reaction, the cross-linking agent reacts with the active groups on the surface of the filler to form a cross-linked network structure, which significantly improves the integrity and stability of the filler, effectively prevents the occurrence of cracking, and does not affect its antibacterial properties. After the reaction is completed, the final modified antibacterial and mildew-proof filler is obtained by filtering, washing, and drying. Embodiment 4,
[0031] The invention provides a technical solution: the antibacterial and mildew-proof filler is composed of the following raw materials in parts by weight: 2.5 parts of nano copper oxide, 2.5 parts of trimethyl octadecylsilane quaternary ammonium salt, 3.5 parts of sepiolite powder and 0.8 parts of vinyl triethoxysilane.
[0032] The antibacterial and mildew-proof filler is prepared by the following steps: B1. Surface modification of nano copper oxide: disperse nano copper oxide in an ethanol solution, perform ultrasonic treatment for 60 minutes to make it uniformly dispersed, then slowly drop vinyl triethoxy silane, and stir and react at 45°C for 3 hours; after the reaction, centrifuge, wash with ethanol 5 times, and dry at 70°C for 3 hours; the concentration of the ethanol solution is 8%; the mass ratio of vinyl triethoxy silane to nano copper oxide is 1:3; this step enables the surface of nano copper oxide to be grafted with vinyl triethoxy silane, improves its compatibility and binding force with organic antibacterial agents and sepiolite powder, and enhances the stability of the antibacterial filler; B2, compounding the antibacterial agent with sepiolite powder, dissolving the organosilicon quaternary ammonium salt antibacterial agent in a toluene solution with a concentration of 15%, adding it to the sepiolite powder, stirring and reacting at 55°C for 4 hours, and the amount of the antibacterial agent is 60% of the mass of the sepiolite powder. After the reaction, vacuum drying is performed at 90°C for 5 hours to fully load the antibacterial agent into the pore structure of the sepiolite powder, forming a composite carrier with antibacterial function; B3. Composite and secondary modification of nano-copper oxide and composite carrier. Add the surface-modified nano-copper oxide to the above-mentioned antibacterial agent and sepiolite powder composite, add ethanol, stir evenly, then drop γ-aminopropyltriethoxysilane, and stir and react at 50°C for 3.5 hours. After the reaction is completed, filter, wash with ethanol 4 times, and dry at 80°C for 4 hours. The concentration of ethanol solution is 8%; the amount of γ-aminopropyltriethoxysilane is 0.5% of the total mass. This step further enhances the bonding force between nano-copper oxide and the composite carrier. At the same time, the introduction of vinyltriethoxysilane helps to improve the dispersibility of the filler in the sole material and has a certain improvement effect on the material's anti-cracking performance; B4, cross-linking modification, the product obtained in the third step is mixed with an isocyanate cross-linking agent in a toluene solution, and stirred at 70°C for 2.5 hours. The isocyanate cross-linking agent is toluene diisocyanate, and the amount is 2% of the total mass; the drying temperature is 90°C, and the drying time is 5 hours. During the reaction, the cross-linking agent reacts with the active groups on the surface of the filler to form a cross-linked network structure, which significantly improves the integrity and stability of the filler, effectively prevents the occurrence of cracking, and does not affect its antibacterial properties. After the reaction is completed, the final modified antibacterial and mildew-proof filler is obtained by filtering, washing, and drying. Embodiment 5,
[0033] The invention provides a technical solution: the antibacterial and mildew-proof filler is composed of the following raw materials in parts by weight: 3 parts of nano copper oxide, 3 parts of trimethyloctadecylsilane quaternary ammonium salt, 4 parts of sepiolite powder and 1 part of vinyl triethoxysilane.
[0034] The antibacterial and mildew-proof filler is prepared by the following steps: B1. Surface modification of nano copper oxide: disperse nano copper oxide in an ethanol solution, perform ultrasonic treatment for 60 minutes to make it uniformly dispersed, then slowly drop vinyl triethoxy silane, and stir and react at 45°C for 3 hours; after the reaction, centrifuge, wash with ethanol 5 times, and dry at 70°C for 3 hours; the concentration of the ethanol solution is 8%; the mass ratio of vinyl triethoxy silane to nano copper oxide is 1:3; this step enables the surface of nano copper oxide to be grafted with vinyl triethoxy silane, improves its compatibility and binding force with organic antibacterial agents and sepiolite powder, and enhances the stability of the antibacterial filler; B2, compounding the antibacterial agent with sepiolite powder, dissolving the organosilicon quaternary ammonium salt antibacterial agent in a toluene solution with a concentration of 15%, adding it to the sepiolite powder, stirring and reacting at 55°C for 4 hours, and the amount of the antibacterial agent is 60% of the mass of the sepiolite powder. After the reaction, vacuum drying is performed at 90°C for 5 hours to fully load the antibacterial agent into the pore structure of the sepiolite powder, forming a composite carrier with antibacterial function; B3. Composite and secondary modification of nano-copper oxide and composite carrier. Add the surface-modified nano-copper oxide to the above-mentioned antibacterial agent and sepiolite powder composite, add ethanol, stir evenly, then drop γ-aminopropyltriethoxysilane, and stir and react at 50°C for 3.5 hours. After the reaction is completed, filter, wash with ethanol 4 times, and dry at 80°C for 4 hours. The concentration of ethanol solution is 8%; the amount of γ-aminopropyltriethoxysilane is 0.5% of the total mass. This step further enhances the bonding force between nano-copper oxide and the composite carrier. At the same time, the introduction of vinyltriethoxysilane helps to improve the dispersibility of the filler in the sole material and has a certain improvement effect on the material's anti-cracking performance; B4, cross-linking modification, the product obtained in the third step is mixed with an isocyanate cross-linking agent in a toluene solution, and stirred at 70°C for 2.5 hours. The isocyanate cross-linking agent is toluene diisocyanate, and the amount is 2% of the total mass; the drying temperature is 90°C, and the drying time is 5 hours. During the reaction, the cross-linking agent reacts with the active groups on the surface of the filler to form a cross-linked network structure, which significantly improves the integrity and stability of the filler, effectively prevents the occurrence of cracking, and does not affect its antibacterial properties. After the reaction is completed, the final modified antibacterial and mildew-proof filler is obtained by filtering, washing, and drying. Embodiment 6,
[0035] The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, which is composed of the following materials in parts by mass: 40 parts of recycled oil bio-based plastic, 20 parts of smoked rubber, 10 parts of modified mixed reinforcing filler prepared in Example 1, 10 parts of calcium powder, 0.5 parts of diisopropylbenzene oxide, 1.0 parts of zinc oxide, 0.5 parts of stearic acid, 1.5 parts of octylated diphenylamine and 4 parts of antibacterial and mildew-proof filler prepared in Example 3; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 30 rpm, the speed of the roller of the open mixer to 10 rpm, and the mixing temperature to 80°C; perform preliminary mixing for 5 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 10 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 10 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 50 rpm and the temperature can be controlled at 100°C. The speed of the open mill roller can be increased to 15 rpm.
[0036] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 10 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 60 rpm and the temperature is 120°C; the speed of the open mill roller is 20 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 150°C, the vulcanization pressure to 10 MPa, and the vulcanization time to 10 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0037] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed. Embodiment 7,
[0038] The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, which is composed of the following materials by weight: 50 parts of recycled oil bio-based plastic, 25 parts of smoked rubber, 13 parts of modified mixed reinforcing filler prepared in Example 1, 15 parts of calcium powder, 0.8 parts of diisopropylbenzene oxide, 1.3 parts of zinc oxide, 0.7 parts of stearic acid, 2 parts of octylated diphenylamine and 5 parts of antibacterial and mildew-proof filler prepared in Example 3; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 50 rpm, the speed of the roller of the open mixer to 15 rpm, and the mixing temperature to 100°C; perform preliminary mixing for 10 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 15 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 15 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 70 rpm and the temperature can be controlled at 120℃; the speed of the open mill roller can be increased to 20 rpm.
[0039] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 15 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 80 rpm and the temperature is 140°C; the speed of the roller of the open mill is 25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 180°C, the vulcanization pressure to 15MPa, and the vulcanization time to 30 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0040] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed. Embodiment 8,
[0041] The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, which is composed of the following materials by weight: 60 parts of recycled oil bio-based plastic, 30 parts of smoked rubber, 15 parts of modified mixed reinforcing filler prepared in Example 1, 20 parts of calcium powder, 1.0 part of diisopropylbenzene oxide, 1.5 parts of zinc oxide, 0.8 parts of stearic acid, 2.5 parts of octylated diphenylamine and 6 parts of antibacterial and mildew-proof filler prepared in Example 3; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 50 rpm, the speed of the roller of the open mixer to 15 rpm, and the mixing temperature to 100°C; perform preliminary mixing for 10 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 15 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 15 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 70 rpm and the temperature can be controlled at 120℃; the speed of the open mill roller can be increased to 20 rpm.
[0042] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 15 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 80 rpm and the temperature is 140°C; the speed of the roller of the open mill is 25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 180°C, the vulcanization pressure to 15MPa, and the vulcanization time to 30 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0043] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed. Embodiment 9,
[0044] The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, composed of the following materials in parts by mass: 40 parts of recycled oil bio-based plastic, 20 parts of smoked rubber, 10 parts of modified mixed reinforcing filler prepared in Example 2, 10 parts of calcium powder, 0.5 parts of diisopropylbenzene oxide, 1.0 parts of zinc oxide, 0.5 parts of stearic acid, 1.5 parts of octylated diphenylamine and 4 parts of antibacterial and mildew-proof filler prepared in Example 4; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 30 rpm, the speed of the roller of the open mixer to 10 rpm, and the mixing temperature to 80°C; perform preliminary mixing for 5 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 10 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 10 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 50 rpm and the temperature can be controlled at 100°C. The speed of the open mill roller can be increased to 15 rpm.
[0045] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 10 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 60 rpm and the temperature is 120°C; the speed of the open mill roller is 20 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 150°C, the vulcanization pressure to 10 MPa, and the vulcanization time to 10 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0046] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed.
[0047] Embodiment 10 The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, composed of the following materials by mass: 50 parts of recycled oil bio-based plastic, 25 parts of smoked rubber, 13 parts of modified mixed reinforcing filler prepared in Example 2, 15 parts of calcium powder, 0.8 parts of diisopropylbenzene oxide, 1.3 parts of zinc oxide, 0.7 parts of stearic acid, 2 parts of octylated diphenylamine and 5 parts of antibacterial and mildew-proof filler prepared in Example 4; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 50 rpm, the speed of the roller of the open mixer to 15 rpm, and the mixing temperature to 100°C; perform preliminary mixing for 10 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 15 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 15 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 70 rpm and the temperature can be controlled at 120℃; the speed of the open mill roller can be increased to 20 rpm.
[0048] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 15 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 80 rpm and the temperature is 140°C; the speed of the roller of the open mill is 25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 180°C, the vulcanization pressure to 15MPa, and the vulcanization time to 30 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0049] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed.
[0050] Embodiment 11, The present invention provides a technical solution: a recycled oil bio-based plastic mixed rubber sole material, which is composed of the following materials by weight: 60 parts of recycled oil bio-based plastic, 30 parts of smoked rubber, 15 parts of modified mixed reinforcing filler prepared in Example 1, 20 parts of calcium powder, 1.0 part of diisopropylbenzene oxide, 1.5 parts of zinc oxide, 0.8 parts of stearic acid, 2.5 parts of octylated diphenylamine and 6 parts of antibacterial and mildew-proof filler prepared in Example 4; A method for preparing a recycled oil bio-based plastic mixed rubber sole material, comprising the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 50 rpm, the speed of the roller of the open mixer to 15 rpm, and the mixing temperature to 100°C; perform preliminary mixing for 10 minutes to evenly mix the two and form a continuous matrix phase; S3. Then add 15 parts of modified mixed reinforcing filler and calcium powder to the above matrix and continue mixing for 15 minutes. During the mixing process, pay attention to the state of the material to ensure that the filler is evenly dispersed in the matrix material. Appropriately adjust the speed and temperature of the mixer. The speed of the internal mixer can be increased to 70 rpm and the temperature can be controlled at 120℃; the speed of the open mill roller can be increased to 20 rpm.
[0051] S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in turn, and mix for another 15 minutes. During the mixing process, ensure that the additives are fully dispersed to avoid agglomeration; at this time, the speed of the internal mixer is maintained at 80 rpm and the temperature is 140°C; the speed of the roller of the open mill is 25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 180°C, the vulcanization pressure to 15MPa, and the vulcanization time to 30 minutes. During the vulcanization process, diisopropylbenzene oxide triggers the cross-linking reaction between the rubber molecular chains, and under the activation of zinc oxide and stearic acid, a stable cross-linked network structure is formed. At the same time, octylated diphenylamine plays an anti-aging role, and the antibacterial and anti-mildew filler plays its antibacterial and anti-mildew function.
[0052] S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed.
[0053] Comparative Example 1: This comparative example is a recycled oil bio-based plastic mixed rubber sole material. The difference from Example 7 is that no modified mixed reinforcing filler is added, and the rest is the same.
[0054] Comparative Example 2: This comparative example is a recycled oil bio-based plastic mixed rubber sole material. The difference from Example 7 is that no antibacterial and anti-mildew filler is added, and the rest is the same.
[0055] The recycled oil bio-based plastic mixed rubber sole materials prepared in Examples 6-8 and Comparative Examples 1-2 were subjected to performance tests, and the test results are shown in Table 1: Table 1:
[0056] As can be seen from Table 1, the recycled oil bio-based plastic mixed rubber sole material of the present invention adds antibacterial and mildew-proof fillers to inhibit the growth and reproduction of bacteria, endow the material with reliable antibacterial properties, improve the antibacterial and antibacterial capabilities, and enhance the comprehensive performance and service life of the sole; the modified mixed reinforced filler is added to increase the flexibility of the entire modified mixed reinforced filler; it can better adapt to the bending, deformation, etc. of the sole during wearing, and improve the wearing comfort and durability of the sole.
[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions. The sentence "includes an element defined by ... does not exclude the existence of other identical elements in the process, method, article or device including the element".
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A recycled oil bio-based plastic mixed rubber sole material, characterized in that: The invention is composed of the following materials in parts by weight: 40-60 parts of recycled oil bio-based plastic, 20-30 parts of smoke glue, 10-15 parts of modified mixed reinforcing filler, 10-20 parts of calcium powder, 0.5-1.0 parts of diisopropylbenzene oxide, 1.0-1.5 parts of zinc oxide, 0.5-0.8 parts of stearic acid, 1.5-2.5 parts of octylated diphenylamine and 4-6 parts of antibacterial and anti-mildew filler; The modified mixed reinforcing filler is prepared by the following steps: A1. Fiber alkali washing and activation: Soak the bamboo fiber and carbon fiber in potassium hydroxide solution for 1-1.5 hours at a temperature of 40-45°C. After soaking, rinse with plenty of water until neutral, and then dry at 80-85°C for 2-2.5 hours. A2, silane coupling agent grafting, adding the dried bamboo fiber and carbon fiber to the silane coupling agent solution, the mass ratio of bamboo fiber to silane coupling agent is 12:1-10:1, the mass ratio of carbon fiber to silane coupling agent is 15:1-13:1, stirring and reacting at 50-55°C for 2-2.5 hours, filtering and washing the fibers after the reaction, and drying at 70-75°C for 1-1.5 hours; A3, copolymerization grafting and cross-linking reaction, the bamboo fiber grafted with silane coupling agent and the carbon fiber are mixed, added into a toluene solution containing butyl acrylate, glycidyl methacrylate mixed monomer, initiator azobisisobutyronitrile and cross-linking agent polyethylene glycol diacrylate, and stirred at 75-80°C for 3-3.5 hours under nitrogen protection; the initiator decomposes to produce free radicals, which then initiates monomer polymerization, the polymer chain continues to grow and is grafted onto the fiber surface, and the polyethylene glycol diacrylate participates in the cross-linking reaction; after the reaction is completed, the fiber is filtered and washed, and dried at 60-65°C for 1-1.5 hours; A4. Surface modification and dispersion treatment: the copolymerized and grafted mixed fiber is placed in an ethanol solution containing stearic acid glyceryl ester, and stirred for reaction at 40-45°C for 1.5-2 hours; after the reaction, the fiber is filtered and washed, and dried at 50-55°C for 1-1.5 hours to obtain a modified mixed reinforcing filler.
2. The recycled oil bio-based plastic mixed rubber sole material according to claim 1, characterized in that: The concentration of the silane coupling agent solution in A2 is 2-3%, wherein the solvent is ethanol.
3. The recycled oil bio-based plastic mixed rubber sole material according to claim 1, characterized in that: The amount of the glycidyl methacrylate mixed monomer in A3 is 25-35% of the total mass of the fiber, the amount of the initiator azobisisobutyronitrile is 0.8-1.2% of the mass of the mixed monomer, and the amount of the crosslinking agent polyethylene glycol diacrylate is 0.4-0.8% of the mass of the mixed monomer.
4. The recycled oil bio-based plastic mixed rubber sole material according to claim 1, characterized in that: The amount of stearyl glyceryl in A4 is 4-8% of the total mass of the fiber; the concentration of the ethanol solution is 4-8%.
5. The recycled oil bio-based plastic mixed rubber sole material according to claim 1, characterized in that: The antibacterial and mildew-proof filler is composed of the following raw materials in parts by weight: 2-3 parts of nano copper oxide, 2-3 parts of trimethyl octadecylsilane quaternary ammonium salt, 3-4 parts of sepiolite powder and 0.5-1 part of vinyl triethoxysilane; The antibacterial and mildew-proof filler is prepared by the following steps: B1. Surface modification of nano copper oxide: disperse nano copper oxide in an ethanol solution, perform ultrasonic treatment for 40-60 minutes to make it uniformly dispersed, then slowly drop vinyl triethoxysilane, stir and react at 40-45°C for 2-3 hours; after the reaction, centrifuge, wash with ethanol 3-5 times, and dry at 60-70°C for 2-3 hours; B2, compounding the antibacterial agent with sepiolite powder, dissolving the organosilicon quaternary ammonium salt antibacterial agent in toluene solution, adding it to the sepiolite powder, stirring and reacting at 50-55°C for 3-4 hours, the amount of the antibacterial agent is 50-60% of the mass of the sepiolite powder, and after the reaction, vacuum drying at 80-90°C for 4-5 hours; B3, composite nano copper oxide with composite carrier and secondary modification, add the surface modified nano copper oxide to the above antibacterial agent and sepiolite powder composite, add ethanol, stir evenly, then drop γ-aminopropyl triethoxysilane, stir and react at 45-50°C for 2.5-3.5 hours, filter after the reaction, wash with ethanol 2-4 times, and dry at 70-80°C for 3-4 hours; B4, cross-linking modification, the product obtained in the third step is mixed with an isocyanate cross-linking agent in a toluene solution, and stirred for reaction at 60-70°C for 1.5-2.5 hours; after the reaction is completed, the final modified antibacterial and mildew-proof filler is obtained by filtering, washing and drying.
6. The recycled oil bio-based plastic mixed rubber sole material according to claim 5, characterized in that: The concentration of the ethanol solution in B1 is 6-8%; the mass ratio of vinyltriethoxysilane to nano-copper oxide is 1:4-1:
3.
7. The recycled oil bio-based plastic mixed rubber sole material according to claim 5, characterized in that: The concentration of the toluene solution in B2 is 10-15%.
8. The recycled oil bio-based plastic mixed rubber sole material according to claim 5, characterized in that: The concentration of the ethanol solution in B3 is 6-8%; the amount of γ-aminopropyltriethoxysilane used is 0.3-0.5% of the total mass.
9. The recycled oil bio-based plastic mixed rubber sole material according to claim 5, characterized in that: The isocyanate crosslinking agent in B4 is toluene diisocyanate, and the amount used is 1-2% of the total mass; the drying temperature is 80-90° C., and the drying time is 3-5 hours.
10. A method for preparing a recycled oil bio-based plastic mixed rubber sole material, characterized in that: Prepared by the following steps: S1. Drying the recycled oil bio-based plastic under constant temperature and humidity conditions to remove the moisture contained therein; S2. Add the dried recycled oil bio-based plastic and tobacco glue into an internal mixer or an open mixer; set the speed of the internal mixer to 30-50 rpm, the speed of the roller of the open mixer to 10-15 rpm, and the mixing temperature to 80-100°C; perform preliminary mixing for 5-10 minutes to evenly mix the two to form a continuous matrix phase; S3, then add 10-15 parts of modified mixed reinforcing filler and calcium powder into the above matrix, and continue mixing for 10-15 minutes; S4, then add diisopropylbenzene oxide, zinc oxide, stearic acid, octylated diphenylamine and antibacterial and mildew-proof filler in sequence, and mix for 10-15 minutes. During the mixing process, ensure that the additives are fully dispersed; at this time, the speed of the internal mixer is maintained at 60-80 rpm, the temperature is 120-140°C; the speed of the open mill roller is 20-25 rpm. After the mixing is completed, a uniform mixed rubber is obtained; S5. Preform the mixed rubber material according to the shape and size requirements of the sole; put the preformed sole into a vulcanizer, set the vulcanization temperature to 150-180°C, the vulcanization pressure to 10-15MPa, and the vulcanization time to 10-30 minutes; S6. After vulcanization is completed, the sole is taken out from the vulcanizer and demoulding is performed.
Citation Information
Patent Citations
Method for preparing rubber plasticizer by using illegal cooking oil
CN103642079A
Degradable bio-based plastic based on modified bamboo powder and preparation method thereof
CN116554664A
Warm mixing regenerant, asphalt mixture and preparation method of warm mixing regenerant
CN118725499A
Reclaimed oil bio-based plastic modified rubber material and preparation method thereof
CN119350751A
Cited By
Modified rubber composite nylon elastomer material and preparation method thereof
CN120904652A
Polyester coated modified bamboo fiber and preparation method thereof
CN121110368A